Mild opening procedure to obtain open-ended yet long single-wall carbon nanotubes for subsequent filling - Aina Fitó-Parera; Miguel Ángel López Carrillo; Marcel Erwan Tonye; Maksiem Erkens; Pegie Cool; Wim Wenseleers; Salomé Forel; Sofie Cambré (Carbon Trends)
Encapsulation of molecules inside the hollow core of single-wall carbon nanotubes (SWCNTs) has become an interesting research field to create new functionalities. To fill the SWCNTs, as-synthesized SWCNTs first need to be opened. Typical opening procedures however include harsh (mechanical or chemical) steps, such as strong acid oxidation, grinding, and sonication, which cut the SWCNTs into much shorter segments. While SWCNTs can be synthesized with lengths up to several micrometers, opened SWCNTs typically show maximum lengths of only a few hundred nanometers, limiting their use for filling with long, one-dimensional arrays of molecules or studying the transport of molecules through their hollow core. Here, we present a mild opening procedure to achieve open, yet long SWCNTs. By comparing different processing steps in their ability to open SWCNTs without significantly reducing the SWCNT length, we present a simple three-step procedure including an air oxidation, a mild acidic treatment, and a high-temperature vacuum annealing, resulting in nearly complete opening of all SWCNTs in a sample, independent of the SWCNT chiral structure and diameter. The procedure has been applied to different SWCNT starting batches to confirm its general applicability. While the opening of SWCNTs is characterized by optical spectroscopy after water filling, statistical SWCNT length distributions are obtained through atomic force microscopy and hyperspectral photoluminescence imaging of SWCNTs. Our results demonstrate that mechanical steps, such as grinding and sonication, can be strictly avoided to obtain a significant fraction of opened SWCNTs with longer lengths.